Agile Governance for Disaster Management in Higher Education: Insights on Literacy, Preparedness, and Student Roles in Ternate - Marthinu, Eva; Salam, Ramdani; Adjam, Syarifuddin; Acmad, Rahim; Rohmah, Putri Adibatur (Journal of Transformative Governance and Social Justice, 2025)
Ternate Island, located in the volcanic area, faces persistent disaster risks from Mount Gamalama’s activity, urbanization pressures, and climate change impacts, requiring adaptive and collaborative governance in higher education disaster management. This descriptive quantitative study surveyed 117 Geography Education students from two universities in disaster-prone areas of Ternate using an online questionnaire to measure participation in disaster training, perceptions of Agile Governance, disaster literacy, and personal preparedness, analyzed through descriptive statistics. Results showed only 42% of students had attended university-led disaster training, while perceptions of Agile Governance averaged 77%, disaster literacy 74%, and preparedness 76%, with the highest score on technology-supported systems (82%) and active policy evaluation involvement (77%). However, dissemination of official disaster information was relatively low (69%), and preparedness practices such as evacuation planning (72%) and storing emergency supplies (76%) were driven more by individual initiative than structured institutional support. These findings suggest a gap between positive perceptions and actual preparedness practices, highlighting the need for systematic interventions. It is recommended that universities integrate mandatory simulation-based disaster training into the academic calendar, strengthen two-way communication channels, utilize digital tools for real-time alerts, and formalize student roles in disaster governance forums. Such measures, aligned with Agile Governance principles, can transform student engagement from passive recipients to proactive actors, fostering a resilient, responsive, and sustainable university disaster management system.